Islamic Republic of Afghanistan - Joint World Bank-IMF Debt Sustainability Analysis - World Bank (World Bank, Washington, DC, 2019)
This debt sustainability analysis (DSA) concludes that Afghanistan’s external and overall risk of debt distress continues to be assessed as high. Afghanistan’s debt sustainability hinges on continued donor grants inflows (currently around 40 percent of GDP) against substantial fiscal and external deficits and downside risks to the economic outlook. A gradual replacement of grants by debt financing leads to high risk of debt distress in the long run and is captured by mechanical risk ratings based on an extended 20-year period rather than the standard 10-year period. Significant downside risks include the fragile security situation, political uncertainty, domestic revenue shortfalls, weather related risks, and regional economic instability. The authorities should continue their efforts to mobilize revenue and implement reforms, while donors should continue to provide financing in the form of grants. Debt management capacity, including the monitoring of contingent liabilities emanating from state-owned entities and public-private partnerships (PPPs), should be strengthened.